Hepatitis B virus DNA integration and transactivation of cellular genes - Kumar, Vijay (Iatreia, 2007)
Chronic hepatitis B virus (HBV) infection is etiologically related to human hepatocellular carcinoma (HCC). Most HCCs contain integrated HBV DNA in hepatocyte, suggesting that the integration may be involved in carcinogenesis. Available data on the integrants from human hepatocellular carcinomas seem to represent primary integrants as well as the products of secondary rearrangements. By means of structural analyses of the possible primary integrants, it has been observed that the replication intermediates of the viral genome are the preferred substrates for integration. The integrated HBV DNA and the target cellular DNA are invariably associated with deletions, possibly reflecting the substrate for, and the mechanism of, the integration reaction. The host DNA sequences as well as the target site of integration in chromosomes are selected randomly suggesting that HBV DNA integration should bring about random mutagenic effects. Analysis of the samples recovered from hepatocellular carcinomas show that the integrated HBV DNA can mediate secondary rearrangements of chromosomes, such as translocations, inversions, deletions and (possibly) amplifications. The integration of HBV DNA into the host genome occurs at early steps of clonal tumor expansion. The integration has been shown in a number of cases to affect a variety of cancer-related genes and to exert insertional mutagenesis. However, in contrast to the woodchuck model, in which specific HBV-DNA integration is detectable in most cases, insertional activation or inactivation of cellular genes appears to be a rare event in man. The discovery of transactivating functions exerted by HBx and truncated HBs(urface) proteins supports the notion that these could be relevant to hepatocarcinogenesis as these transactivator sequences have been found in a large number of HCC tumors or hepatoma-derived cell lines. The HBx transactivator can stimulate a wide range of cellular genes and displays oncogenic potential in cell culture as well as in a transgenic environment. The HBs transactivators are encoded by the preS/S region of S gene and may involve carboxy terminal truncation to gain transactivation function. Expression of host genes by viral transactivators is mediated by regulatory elements of the cellular transcription factors like c-fos, c-myc, NF-kappa B, SRE and Sp1. Thus, during hepatitis B infection, the tendency of rearrangement of hepatocyte chromosomes is combined with the forcible turnover of cells. This is a constantly operating system for the selection of cells that grow better than normal cells, possibly involving important steps in multi-staged hepatocarcinogeneses. Gene expression profiling and proteomic techniques may help to characterize the molecular mechanisms driving HBV-associated carcinogenesis, and thus potentially identify new strategies in diagnosis and therapy. REFERENCES 1. Kekule AS, Lauer U, Meyer M, Caselmann WH, Hofschneider PH, Koshy R. (1990) The preS2/S region of integrated hepatitis B virus DNA encodes a transcriptional transactivator. Nature 343, 457-461. 2. Caselmann WH. (1996) Trans-activation of cellular genes by hepatitis B virus proteins: a possible mechanism of hepatocarcinogenesis. Adv Virus Res 47, 253-302. 3. Matsubara K, Tokino T. (1990) Integration of hepatitis B virus DNA and its implications for hepatocarcinogenesis. Mol Biol Med. 7, 243-60. 4. Peng Z, Zhang Y, Gu W, Wang Z, Li D, Zhang F, Qiu G, Xie K. (2005) Integration of the hepatitis B virus X fragment in hepatocellular carcinoma and its effects on the expression of multiple molecules: a key to the cell cycle and apoptosis. Int J Oncol 26, 467-473. 5. Ramesh R, Panda SK, Jameel S, Rajasambandam P. (1994) Mapping of the hepatitis B virus genome in hepatocellular carcinoma using PCR and demonstration of a potential trans-activator encoded by the frequently detected fragment. J Gen Virol. 75, 327-334.